2023
DOI: 10.1007/s12325-023-02528-8
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Body Surface Area and Itch Severity Define Response to Baricitinib in Patients with Moderate-to-Severe Atopic Dermatitis at Week 16

Abstract: Introduction Atopic dermatitis (AD) is a chronic, inflammatory skin disease characterized by heterogeneous clinical phenotypes and high symptom burden, especially through itch. Baricitinib (BARI), an oral Janus Kinase 1/2 inhibitor, is approved in Europe, Japan, and other countries, for treatment of adults with moderate-to-severe AD who are candidates for systemic therapy. This post hoc analysis of a Phase 3 topical corticosteroid (TCS) combination therapy trial (BREEZE-AD7) aims to characterize p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…These detailed insights further support individualized patient management and may ultimately help patients access therapies to which they are most likely to respond. As previously reported [8], the BARI itchdominant patient presents with a profound burden at baseline; the mean EASI total score is 20.5, with over one third of the sample exhibiting severe AD (score > 21) and some reaching as high as 30.5. Additionally, this patient subtype presents with severe itch (mean Itch Fig.…”
Section: Easi75 Response Rates Over 16 Weeks In Patients With Bsa ≤ 4...supporting
confidence: 72%
“…These detailed insights further support individualized patient management and may ultimately help patients access therapies to which they are most likely to respond. As previously reported [8], the BARI itchdominant patient presents with a profound burden at baseline; the mean EASI total score is 20.5, with over one third of the sample exhibiting severe AD (score > 21) and some reaching as high as 30.5. Additionally, this patient subtype presents with severe itch (mean Itch Fig.…”
Section: Easi75 Response Rates Over 16 Weeks In Patients With Bsa ≤ 4...supporting
confidence: 72%
“…Moreover, dupilumab showed lower effectiveness in patients with significant head, neck, and hand involvement, as recently described by Chiricozzi et al [ 16 ]. On the other hand, baricitinib appears to be more effective in these areas, as described by Thyssen et al [ 17 ]…”
Section: Resultsmentioning
confidence: 88%
“…No agreement was obtained in the first round for statement 2, which concerned the preferable use of JAK inhibitors over biologics in patients with severe itch. This statement was rewritten according to the members’ suggestions, shifting the focus to the “itch-dominant” phenotype (patients with itch-NRS ≥ 7 and BSA up to 40%) [ 17 ], obtaining the agreement during the second Delphi round.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subset of AD patients of special relevance are known as the ‘itch‐dominant phenotype’, who appear to require greater medical attention 24 . It has recently been demonstrated that these patients, defined as having itch NRS ≥7 and 10%–40% affected BSA, are precisely those who are most likely to benefit from baricitinib 25 …”
Section: Discussionmentioning
confidence: 99%